Reduced sleep pressure in young children with autism. Issue 6 (18th December 2019) - Arazi, Ayelet; Meiri, Gal; Danan, Dor; Michaelovski, Analya; Flusser, Hagit; Menashe, Idan; Tarasiuk, Ariel; Dinstein, Ilan
Abstract: Study Objectives: Sleep disturbances and insomnia are highly prevalent in children with Autism Spectrum Disorder (ASD). Sleep homeostasis, a fundamental mechanism of sleep regulation that generates pressure to sleep as a function of wakefulness, has not been studied in children with ASD so far, and its potential contribution to their sleep disturbances remains unknown. Here, we examined whether slow-wave activity (SWA), a measure that is indicative of sleep pressure, differs in children with ASD. Methods: In this case-control study, we compared overnight electroencephalogram (EEG) recordings that were performed during Polysomnography (PSG) evaluations of 29 children with ASD and 23 typically developing children. Results: Children with ASD exhibited significantly weaker SWA power, shallower SWA slopes, and a decreased proportion of slow-wave sleep in comparison to controls. This difference was largest during the first 2 hours following sleep onset and decreased gradually thereafter. Furthermore, SWA power of children with ASD was significantly negatively correlated with the time of their sleep onset in the lab and at home, as reported by parents. Conclusions: These results suggest that children with ASD may have a dysregulation of sleep homeostasis that is manifested in reduced sleep pressure. The extent of this dysregulation in individual children was apparent in the amplitude of their SWA power, which was indicative of the severity of their individual sleep disturbances. We, therefore, suggest that disrupted homeostatic sleep regulation may contribute to sleep disturbances in children with ASD.